THE COST AND EFFICIENCY ANALYSIS OF JUVENILE VOCATIONAL CENTER - Nantiwatkun, Natthaprat; Kosalakorn Permpoonwiwat, Chompoonuh; Sukharom, Renu (RMUTT Global Business and Economics Review, 2022)
The objectives of this research are as follows: 1) an analysis of cost; and 2) an analysis of economy of scale. This study uses a mixed research method that consists of quantitative and qualitative research. The study uses 2 data sets from the Juvenile Vocational Center: 1) the data related to the monthly costs of 17 Juvenile Vocational Centers according to governmental accounting from September 2016 to December 2019, with a total of 680 samples from 16,000 youths; and 2) group discussions are qualitative data collection tools. The data is collected from 30 observation subjects in 4 centers. The total cost equations are estimated using econometric methods. The results reveal that an economy of scale does not appear within the operations of small and large centers. An inefficient resource allocation occurs in large centers. The minimum long-term average cost is 5,400 baht, about 500 youths. This cost is inappropriate for the workload as it is lower than the average standard living cost. The authority should allocate a budget for the center by using a minimum average cost of a small center.